Identification and Analysis of RNA Editing Events in Ovarian Serous Cystadenoma Using RNA-seq Data - Wang, Yulan; Song, Xiaofeng; Xu, Tianyi (Current Gene Therapy, 2021)
Background: Recent studies have revealed thousands of A-to-I RNA editing events in primates. These events are closely related to the occurrence and development of multiple cancers, but the origination and general functions of these events in ovarian cancer remain incompletely understood. Objective: To further the determination of molecular mechanisms of ovarian cancer from the perspective of RNA editing. Methods: Here, we used the SNP-free RNA editing Identification Toolkit (SPRINT) to detect RNA editing sites. These editing sites were then annotated, and related functional analysis was performed. Results: In this study, about 1.7 million RES were detected in each sample, and 98% of these sites were due to A-to-G editing and were mainly distributed in non-coding regions. More than 1,000 A– to-G RES were detected in CDS regions, and nearly 700 could lead to amino acid changes. Our results also showed that editing in the 3′UTR regions could influence miRNA-target binding. We predicted the network of changed miRNA-mRNA interaction caused by the A-to-I RNA editing sites. We also screened the differential RNA editing sites between ovarian cancer and adjacent normal tissues. We then performed GO and KEGG pathway enrichment analysis on the genes that contained these differential RNA editing sites. Finally, we identified the potential dysregulated RNA editing events in ovarian cancer samples. Conclusion: This study systematically identified and analyzed RNA editing events in ovarian cancer and laid a foundation to explore the regulatory mechanism of RNA editing and its function in ovarian cancer.
Keywords: ovarian cancer